EFECT OF ALGINATE ADDITION FROM Sargassum binderi IN PRODUCTION BROWN RICE MILK - Nur Latifah, Rais
ABSTRACT EFECT OF ALGINATE ADDITION FROM Sargassum binderi IN PRODUCTION BROWN RICE MILK By Rais Nur Latifah NIM. 20515051 (Chemistry Magister Study Program) Brown rice milk is potential to cure beri-beri disease and suggested as a vegetable milk for autism or lactose intolerance patients. Brown rice milk can be used as alternative milk due to its similar nutrition to regular cow’s milk and goat’s milk. Brown rice milk had not flavor as milk and emulsion stability not well now. The less of milk with added biofilm which was a combination of glycerine and alginate from Sargassum binderi. Alginate was extracted with non acidic method that CaCl2 (b/v) with EDTA addition. Characterization of alginate fungsional group determined using FTIR (Fourier Transform InfraRed). Two types of brown rice milk in this research was SBM I (milk of brown rice) and SBM II (milk of porridge brown rice) with comparison between brown rice or porridge brown rice and water was 1:15 and 1:30 (w/v). Variation of alginate concentration was treated forwards optimized milk by adding comparation (w/v) (0,05%; 0,1%; 0,2%; 0,4%; 0,6%; 0,8%; 1,0% dan 1,2%). Optimation of brown rice milk was chosen by determining then nutrition value (carbohydrate with Luff Schroll method, lipid with gravimetric method, protein with Kjeldahl method, food fiber with enzyme method), milk stabilization (analysis of texture milk with microscope and milk sedimentation rate) and self life of product (pH, degradation of colour substance, micrbobe analysis). The result was compared to commercial brown rice milk. Sargassum binderi collected from Sayang Heulang beach, Pameungpeuk, Garut, West Java contained 6.25% (w/w) of alginate with water content 12.2%. The characteristics peaks of alginate appeared at 3477, 1633, 1419 and 1614 cm-1, corresponding to hydroxyl (OH), carbonyl (C=O), carboxyl (COOH) and Na in alginate, respectively. Alginate with 0,1% (w/v) had density 1,007 g/mL and viscocity 7.6x10-3 kg m-1 s-1. Based on analysis from two types of brown rice milk was resulted optimal brown rice milk that SBM I= 1:15 with high carbohydrate and lipid contents was 36.32 mg/mL milk (w/v) and 0.034 mg/mL milk (w/v) with self life 9 days (pH 7,04). Optimal addition of alginate was 0.2% (w/v) and increased good emulsion stabilization. Analysis of nutrition value was 40.21 mg carbohydrates/mL milk (w/v), 1.30 mg protein/mL milk (w/v), 0.16 mg lipids/mL milk (w/v), 18.9 mg total fiber/mL milk (w/v), respectively. Analysis of milk texture showed particle of brown rice milk which coloids. The stability of the emulsion increases with the change of the milk sedimentation rate from order 2 to order 1 with the rate constant of 0.3528 turbid/day-1 to 0.067 days-1 with a half-life of 9 days 3 hours to 10 days 7 hours. iv The shelf life of milk increased from 9 days to 15 days (pH 7,01 and did not microbe) with 4oC storage. The addition of alginate is also able to inhibit degradation rate of dairy of brown rice milk from order 1 to order 0 with change of rate constant from 0.052 days-1 to 0.0022 abs/day-1 with half life for 3 days 4 hours to 7 days.Organoleptic analysis showed the level of